2007
DOI: 10.1007/s10867-007-9045-0
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Domain Analysis to Identify Neurological Disorders from Evoked EMG Responses

Abstract: Evoked EMG M-responses obtained from the thenar muscle in the palm by electrical stimulation of the median nerve demonstrate a well-established smooth bipolar shape for normal healthy subjects. Kinks in this curve are observed in certain neurological disorders and preliminary work suggests their relationship to cervical spondylosis. The present work was taken up to develop an objective method for the identification of such neurological disorders for automated diagnosis by analysing the M-responses. A Fourier t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Therefore, 107 features encompassing seventy-five t-domain, sixteen f-domain, and ten statistical features were derived for each PPG signal along with six demographic data. The t-domain, f-domain, and statistical features were identified from different previous works [3,4,9,23,[25][26][27]38,39]. It is reported in the literature that 1-24 and 42-58 features were used in PPG related works [49].…”
Section: Feature Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, 107 features encompassing seventy-five t-domain, sixteen f-domain, and ten statistical features were derived for each PPG signal along with six demographic data. The t-domain, f-domain, and statistical features were identified from different previous works [3,4,9,23,[25][26][27]38,39]. It is reported in the literature that 1-24 and 42-58 features were used in PPG related works [49].…”
Section: Feature Extractionmentioning
confidence: 99%
“…Several t-domain features, which were calculated from the original signal and its derivatives, were used by different groups [9,[36][37][38]. In a different study, Zaid et al [39] showed the use of frequency domain features for identifying neurological disorder and in this study, the authors have taken inspiration from Zaid et al to create features in estimating BP accurately from the PPG signal.…”
Section: Introductionmentioning
confidence: 99%
“…The automatic decomposition EMG (ADEMG) method [ 101 ] and the algorithm of precision decomposition [ 102 ] are techniques for decomposing EMG signals. In the case of EMG signal quantification, frequency domain [ 103 ] and time domain [ 104 , 105 ] analysis have been used. In general, the collected EMG potentials are used for the diagnosis of muscle diseases.…”
Section: Electrophysiological Signal Sensingmentioning
confidence: 99%